REQUIREMENTS TO THE METHOD OF TEACHING PHYSICS IN THE CONDITIONS OF THE CREDIT-MODULAR EDUCATION SYSTEM (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
The article considers the main requirements for the methodology of teaching physics in a credit-modular system, when the education system is being reoriented from a knowledge-based to a competency-based approach.